THE ROLE OF BUSINESS PLANNING IN THE DECISION OF PROBLEMS OF STIMULATION OF INNOVATIVE PROCESSES IN CONSTRUCTION MANAGEMENT - V. Bobylev (Publishing House of the State University of Management, 2016)
The article discusses important problems of improving methods of business planning at the organization of management of the modern capital construction. Especially attention is paid to the process of business planning of innovative development of the domestic productive apparatus, the result of which is to increase the competitiveness of domestic products in foreign and domestic market, possibility of the complete solution of comprehensive problems of import substitution in the near future.